Legal Relations of Contemporary Islamic Family: A Study of The Existence of Local Culture in Sambas, West Kalimantan - Asman, Asman; Nilhakim, Nilhakim; Kotyazhov, Andrey V. (IAIN Manado, 2024)
This research investigates marriage laws in Islam, aiming to explore the scientific knowledge of Islamic family law related to the local Sambas culture in marriage practices. The people of Sambas deeply intertwine their regional loyalties with local customary culture, particularly in the context of Muslim weddings. This study addresses whether Islamic marriage laws conflict with local cultural traditions, especially within Indonesia's framework of Islamic family law. The focus of this research examines how the implementation of Islamic marriage laws interacts with or conflicts with the local Sambas culture. The research employs a qualitative methodology that combines fieldwork and literature review. The empirical normative approach is designed to describe data related to contemporary Islamic family law legislation in the context of the local cultural axiology of Sambas, West Kalimantan. This approach systematically examines and explains the facts and characteristics of the subject in detail and depth. The researcher closely ties the research methods to the procedures, techniques, tools, and designs used throughout the study. The primary finding of this research underscores that culture is fundamentally a product of human intellect, comprising patterns, ways of thinking, emotions, and reactions shaped by and expressed through symbols created collectively by the Sambas community. The study identifies significant issues in the current legislative framework, where policymakers often prioritize intellectual subjectivity over human objectivity. As a result, emerging policies fail to address societal needs adequately. In response, the researcher catalogs various forms of local wisdom within Islamic communities in Sambas, proposing these as relevant methodologies for establishing laws that align with local culture.